Horse collar: a rare case report of Madelung disorder with review of literature - Metgudmath, Rajendra B.; Kallur, Pallavi; V. Hattiholi, Virupaxi (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Multiple symmetric lipomatosis is a rare disorder of fat metabolism which is characterized with bilateral symmetric and usually painless masses at various anatomical sites. Generally, the patient with this disease presents with cosmetic deformities. Extensive masses are known to have compressive symptoms like breathing difficulty and dysphagia. Imaging plays a pivotal role diagnosing this condition. Treatment options include both surgical and non-surgical modalities along with management of other metabolic disorders like diabetes and abstaining from alcohol intake. Recurrence is common. Given the uncommon nature of this illness and the debates surrounding its management, we report a case of multiple symmetric lipomatosis.